An Overview of Systematic Reviews: Complementary Therapies for Cancer Patients. (December 2019) - Lee, Seong Min; Choi, Ho Cheol; Hyun, Min Kyung
Introduction: This article critically examines the systematic reviews (SR) and meta-analysis (MA) of complementary therapies for cancer patients to appraise the evidence level, and offers suggestions for future research and practice.Methods: The Cochrane Library and MEDLINE were searched from their inception to January 2018, to identify SR and MA of complementary therapies available for cancer patients. Final selected SR and MA were methodologically evaluated for their quality by applying the Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR2) instrument. Data extraction and risk of quality assessments were performed by 2 independent reviewers.Results: A total of 104 studies were included in the analysis. The majority of the individual clinical trials included in the SR and MA were performed in China (48%) and the United States (26.9%). Breast cancer was the most studied cancer type (25%), and acupuncture was the most studied intervention (21%). Side effects of cancer such as pain, depression, and fatigue were effectively managed with complementary therapies. The methodologically problematic items included not listing the excluded studies and lack of protocol or protocol registration.Conclusions: With increasing interest in research, complementary therapies appear to be beneficial in reducing side effects and raising the quality of life of cancer patients. Complementary therapies have generally been studied for all cancers, with acupuncture being the most researched, regardless of the cancer type. Since AMSTAR2 is a stricter assessment tool than before, future studies need to consider the risk of methodological bias with caution and discuss appropriate overall quality assessment tools.